Comparative study of the inflorescence, spikelet and flower development in species of Cynodonteae (Chloridoideae, Poaceae) - Pilatti, Vanesa (2019)
Inflorescence morphology in Poaceae subtribes Hilariinae, Monanthochloinae, Boutelouinae, Scleropogoninae and Muhlenbergiinae (Cynodonteae, Chloridoideae) has been revisited recently, but inflorescence development remains largely unexplored. The aim of this study is to contribute additional information on the development of inflorescences in Cynodonteae by generating data on Distichlis, Bouteloua, Munroa, Erioneuron and Muhlenbergia and to compare them with results for other grasses. Using scanning electron microscopy images, we identified common developmental patterns among grasses and described developmental novelties for Bouteloua, Distichlis and Muhlenbergia. Novel developmental features are: the amphipetal initiation of second-order branches along the inflorescence of B. curtipendula, the elongation of the internodes of the inflorescence branches before floral development in M. asperifolius and ‘Type II’ unisexual flowers in D. acerosa. Variable traits among studied species are: inflorescence symmetry, direction of branch and spikelet initiation and differentiation, number of developing stamens, glume developmental patterns and timing of the arrest of gynoecium development during the formation of unisexual flowers. Our results allow us to postulate that a delicate balance of phytohormones may direct early development of grass inflorescence branching system by controlling direction of first-order branch differentiation. The approach used here provides a link between definitive structures and the underlying genetics.